2007
DOI: 10.1007/s11883-007-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for obesity

Abstract: Obesity is a chronic metabolic disorder that affects one third of American adults. Modest weight losses of just 5% to 10% of body weight, which are achievable with lifestyle modification and pharmacotherapy, can lead to remarkable improvements in many obesity-associated co-morbidities, including dyslipidemia, hypertension, and type 2 diabetes. In this review, the indications for pharmacotherapy and the goals of treatment are discussed, and current and future pharmacologic approaches to the treatment of obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…If verified, it may be suggested that attention be directed to improving response to COH. In obese poor responders, weight reduction and any other intervention aiming at correcting the hormonal or metabolic derangements associated with obesity [20,21] should be vigorously applied before proceeding with COH for IVF.…”
Section: Discussionmentioning
confidence: 99%
“…If verified, it may be suggested that attention be directed to improving response to COH. In obese poor responders, weight reduction and any other intervention aiming at correcting the hormonal or metabolic derangements associated with obesity [20,21] should be vigorously applied before proceeding with COH for IVF.…”
Section: Discussionmentioning
confidence: 99%
“…It improves glycemic control, slows gastric emptying, decreases food intake, enhances satiety, and reduces body weight when used to treat type 2 diabetes (Johns, 2007). In addition to improved hemoglobin A1C, the patients exhibited dose-dependent weight losses of 2.8 kg in the 10 μg group and 1.6 kg in the 5 μg group (Neff & Aronne, 2007). The most common side effects are nausea, diarrhea, and vomiting.…”
Section: Glucagon-like Peptide-1 Analogsmentioning
confidence: 97%
“…Exenatide and liraglutide are injectable antidiabetic medications that are glucagon-like peptide-1 analogs that increase insulin secretion and suppress glucose-dependent glucagon release (Neff & Aronne, 2007). Exenatide is FDA approved for patients with type 2 diabetes who have failed to achieve adequate glycemic control on oral antidiabetic medications.…”
Section: Glucagon-like Peptide-1 Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug therapy of obesity (orlistat and sibutramine) [46] has not shown a direct beneficial effect on the liver independent of the beneficial effect of weight loss. However, these drugs may enhance the beneficial effects of behavioral therapy.…”
Section: Treatment Of Nafld/nashmentioning
confidence: 99%